Mixed- versus predilution hemodiafiltration effects on convection volume and small and middle molecule clearance in hemodialysis patients: a prospective randomized controlled trial - Kyoung Sook Park; Ea Wha Kang; Tae Ik Chang; Wonji Jo; Jung Tak Park; Tae-Hyun Yoo; Shin-Wook Kang; Seung Hyeok Han (The Korean Society of Nephrology, 2021)
Background The use of newly developed mixed-dilution hemodiafiltration (HDF) can supplement the weaknesses of pre- and postdilution HDF. However, it is unclear whether mixed-HDF performs well compared to predilution HDF. Methods We conducted a prospective, open-labeled, randomized controlled trial from two hemodialysis centers in Korea. Between January 2017 and September 2019, 60 patients who underwent chronic hemodialysis were randomly assigned at a 1:1 ratio to receive either predilution HDF (n = 30) or mixed-HDF (n = 30) for 6 months. We compared convection volume, changes in small- and medium-sized molecule clearance, high-sensitive C-reactive protein (hs-CRP) level, and dialysis-related parameters between the two dialysis modalities. Results A mean effective convection volume of 41.0 ± 10.3 L/session in the predilution HDF group and 51.5 ± 9.0 L/session in the mixed-HDF group was obtained by averaging values of three time-points. The difference in effective convection volume between the groups was 10.5 ± 1.3 L/session. This met the preset noninferiority criteria, suggesting that mixed-HDF was noninferior to predilution HDF. Moreover, the β2-microglobulin reduction rate was greater in the mixed-HDF group than in the predilution HDF group, while mixed-HDF provided greater transmembrane pressure. There were no significant between-group differences in Kt/V urea levels, changes in predialysis hs-CRP levels, proportions of overhydration, or blood pressure values. Symptomatic intradialytic hypotension episodes and other adverse events occurred similarly in the two groups. Conclusion Use of mixed-HDF was comparable to predilution HDF in terms of delivered convection volume and clinical parameters. Moreover, mixed-HDF provided better β2-microglobulin clearance than predilution HDF.